The effect of dictogloss technique on receptive and productive vocabulary improvement: the case of Libyan EFL tertiary learners - Alkurtehe, Khaled Ali M (2021)
This research focused on the effects of the written and oral dictogloss technique on receptive and productive vocabulary development, retention and vocabulary learning strategies at the Libyan university among EFL undergraduate students. This research focused on the effects of the written and oral dictogloss technique on receptive and productive vocabulary development, retention and vocabulary learning strategies at the Libyan university among EFL undergraduate students A quantitative methodology was employed, in which a quasi-experimental design comprising a pretest, a posttest, and a delayed posttest was followed by a questionnaire. Research participants comprised of 64 university undergraduates who were divided into experimental and control groups. The intervention took four weeks to investigate the effect of dictogloss techniques on vocabulary development and vocabulary learning strategies. A paired sample and an independent sample T-test were used to determine the significant differences among the quantitative data in the experiment and the questionnaire. The results indicated there is a `significant effect of oral and written dictogloss techniques on receptive and productive vocabulary development and retention among EFL Libyan undergraduate students. The results also revealed that there is a significant difference in oral and written receptive and productive vocabulary development and retention among EFL students with and without dictogloss intervention. However, the results found that there is no significant difference between receptive and productive vocabulary development as well as retention in oral and written groups among the students. The results point out that there are significant differences between the experimental and the control groups in vocabulary learning strategies among EFL Libyan undergraduate students. The results display that there are significant differences between females and males in the experimental group on vocabulary learning strategies among EFL Libyan students. Finally, this study concluded that the dictogloss technique improved the EFL vocabulary of the university students at the English department in Libya.